If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28 + 3y + -9 = 16y + -13 + -5y Reorder the terms: 28 + -9 + 3y = 16y + -13 + -5y Combine like terms: 28 + -9 = 19 19 + 3y = 16y + -13 + -5y Reorder the terms: 19 + 3y = -13 + 16y + -5y Combine like terms: 16y + -5y = 11y 19 + 3y = -13 + 11y Solving 19 + 3y = -13 + 11y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-11y' to each side of the equation. 19 + 3y + -11y = -13 + 11y + -11y Combine like terms: 3y + -11y = -8y 19 + -8y = -13 + 11y + -11y Combine like terms: 11y + -11y = 0 19 + -8y = -13 + 0 19 + -8y = -13 Add '-19' to each side of the equation. 19 + -19 + -8y = -13 + -19 Combine like terms: 19 + -19 = 0 0 + -8y = -13 + -19 -8y = -13 + -19 Combine like terms: -13 + -19 = -32 -8y = -32 Divide each side by '-8'. y = 4 Simplifying y = 4
| ax^2-8x+5=0 | | -4.1x-2=-3.6x+7 | | 4x+11=-106-9x | | 4x-12+x=0 | | 4x+5x-3=15 | | 13x+5-4x=23 | | 7n+2+3n=12 | | -(50-80)= | | 12c-8-5c=27 | | 8b+4b-b=55 | | 2x-19=12x-53 | | 13+5b-2b=37 | | -50+80= | | 8a+7-5a=31 | | 2n-11=-6+n | | 2(2z-1)-2(5-3z)=2 | | 9c+4c-c=48 | | 6y-4y+y=18 | | 3x-12=2(x-3) | | -50-80=what | | 4a+9a-6a=42 | | -8(n+2)+19=-5n-9 | | 15-2b=-8(2b+2)+3 | | 3l+2=-l-2 | | (4x+5y+-6)*3= | | -18-5x=-(3+8x) | | (12x+15)(12X-15)=144x-225 | | 3ay-6a+7y-14=0 | | (8x+9)(8x-9)=64x-81 | | 4x^3-28x+40x=0 | | 142-5x=22x+19 | | 3-6x=12+3x |